Government Transparency and Public Accountability in the Implementation of Good Governance in Indonesian Constitutional Law System - Muhammad Ngazis (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to analyze the role of government transparency and public accountability in the implementation of Good Governance in the Constitutional Law System in Indonesia. In the context of legal and government dynamics, transparency and accountability are considered the main pillars in achieving effective Good Governance practices. This research used library research method, with a series of research relating to library data collection methods, or research whose research objects areexplored through a variety of library information including books, encyclopaedias, scientific journals and documents. Byfocusing on key aspects of Good Governance such as transparency, accountability, community participation andjustice, this research aims to provide a holistic picture of the implementation of these principles. This research finallyleads to recommendations for strengthening regulations related to transparency, increasing access to publicinformation, and designing accountability mechanisms that are clearer and consistently applied. It is hoped that thesefindings can contribute to further understanding of how transparency and accountability play a role in establishingGood Governance in the Constitutional Law System in Indonesia.